Examining Undergraduate Student Engagement in Construction Law Course: An Empirical Study of Three Universities in Indonesia - Hansen, Seng; Saleh, Nursyam; Apwiddhal (Journal of Engineering Education Transformations, 2025)
This paper reports on an examination of the study characteristics and learning methodologies of undergraduate construction engineering and management students towards legal aspects in the construction sector. While law plays an important role in the implementation of the construction sector, not many universities in Indonesia provide courses related to law for construction and civil engineering students. By applying a longitudinal study of construction law teaching at three universities in Indonesia, this paper explores student engagement with the course, including the course design, the teaching method, the perceptive benefits, and the challenges of participating in the construction law course. Data was collected through observations and questionnaire surveys. Furthermore, the interest in taking the course is also discussed. This paper contributes by providing a rationale for evaluating the effectiveness of law teaching to construction and civil engineering students which can be utilized for further improvement of the teaching and learning of construction law in Indonesia as well as a global audience.